Absorbable metal stents for vascular use in pediatric cardiology: progress and outlook - McLennan, Daniel I.; Maldonado, Jennifer R.; Foerster, Susan R.; Handler, Stephanie S.; LaDisa, John F.; Gudausky, Todd M.; Guillory, Roger J. (Frontiers in Cardiovascular Medicine, 2024)
The past five years have yielded impressive advancements in fully absorbable metal stent technology. The desired ultimate ability for such devices to treat a vascular stenosis without long-term devicerelated complications or impeding future treatment continues to evoke excitement in clinicians and engineers alike. Nowhere is the need for fully absorbable metal stents greater than in patients experiencing vascular anomalies associated with congenital heart disease (CHD). Perhaps not surprisingly, commercially available absorbable metal stents have been implanted in pediatric cardiology patients with conditions ranging from pulmonary artery and vein stenosis to coarctation of the aorta and conduit/shunt reconstructions. Despite frequent short term procedural success, device performance has missed the mark with the commercially available devices that have been implanted to date by not yet being fully absorbable or degrading too quickly for a given application. In this review we first provide a general overview detailing the theory of absorbable metal stents, and then review recent clinical use in CHD patients since the release of current-generation absorbable metal stents around 2019. We also discuss the challenges and our center's experience associated with the use of absorbable metal stents in this pediatric population. Lastly, we present potential directions for future engineering endeavors to mitigate existing challenges.